2006
DOI: 10.1111/j.1365-2966.2006.10283.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances for Hf 2-2, a planetary nebula with the strongest-known heavy-element recombination lines

Abstract: We present high-quality optical spectroscopic observations of the planetary nebula (PN) Hf 2-2. The spectrum exhibits many prominent optical recombination lines (ORLs) from heavy-element ions. Analysis of the H I and He I recombination spectrum yields an electron temperature of ∼900 K, a factor of 10 lower than given by the collisionally excited [O III] forbidden lines. The ionic abundances of heavy elements relative to hydrogen derived from ORLs are about a factor of 70 higher than those deduced from collisio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
149
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(171 citation statements)
references
References 29 publications
18
149
4
Order By: Relevance
“…In PNe, these estimatives show high values. As examples, Liu et al (2006) found t 2 ≈ 0.14 for Hf 2-2, and Krabbe & Copetti (2006) found t 2 ≈ 0.09 for NGC 3242 and NGC 7009 to obtain consistent O ++ /H + estimates derived from RLs and CELs. A discrete estimation of t 2 on the plane of the sky can be computed from point-to-point measurements of temperature, following the procedure proposed by Liu (1998).…”
Section: Magnitude Of the Electron Temperature Fluctuationsmentioning
confidence: 73%
“…In PNe, these estimatives show high values. As examples, Liu et al (2006) found t 2 ≈ 0.14 for Hf 2-2, and Krabbe & Copetti (2006) found t 2 ≈ 0.09 for NGC 3242 and NGC 7009 to obtain consistent O ++ /H + estimates derived from RLs and CELs. A discrete estimation of t 2 on the plane of the sky can be computed from point-to-point measurements of temperature, following the procedure proposed by Liu (1998).…”
Section: Magnitude Of the Electron Temperature Fluctuationsmentioning
confidence: 73%
“…Liu et al (2006) presented an extreme abundance discrepancy factor (ADF) of about 70 for this nebula (the typical ADF is ∼ 2 for most PNe). The ADF is a quantification of the abundance discrepancy, found in PNe and HII regions, between abundances determined from optical recombination lines and those found from collisionally excited lines (Liu 2006).…”
Section: Hf 2-2 (Png0051-089)mentioning
confidence: 92%
“…Owing to this procedure, the RLs abundances for PNe should be considered as only indicative. Liu et al (2006) report that for most galactic PNe, ADFs are in the range of 1.6 to 3. Likewise, Peimbert et al (1995a) determined ADFs for many galactic PNe and computed similar ADF values.…”
Section: Observational Constraintsmentioning
confidence: 99%